1999
DOI: 10.1128/mcb.19.2.1092
|View full text |Cite
|
Sign up to set email alerts
|

Two Polymorphic Variants of Wild-Type p53 Differ Biochemically and Biologically

Abstract: The wild-type p53 protein exhibits a common polymorphism at amino acid 72, resulting in either a proline residue (p53Pro) or an arginine residue (p53Arg) at this position. Despite the difference that this change makes in the primary structure of the protein resulting in a difference in migration during sodium dodecyl sulfate-polyacrylamide gel electrophoresis, no differences in the biochemical or biological characteristics of these wild-type p53 variants have been reported. We have recently shown that p53Arg i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
539
4
28

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 634 publications
(588 citation statements)
references
References 32 publications
17
539
4
28
Order By: Relevance
“…Transient transfection of the various constructs together with a plasmid encoding the green fluorescent protein (eGFP), which served as a control for transfection efficiency, into the p53 null human H1299 cells resulted in the efficient and approximately equal expression of all chimaeric proteins ( Figure 1c). As noted in previous studies (Thomas et al, 1999), 72R polymorphic variant migrated faster than the 72P form, even when in the chimaeric form (Figure 1c), indicating that the chimaerism has not altered this biochemical property of the polymorphs.…”
Section: Generation Of Human-mouse P53 Chimaeric Constructssupporting
confidence: 82%
“…Transient transfection of the various constructs together with a plasmid encoding the green fluorescent protein (eGFP), which served as a control for transfection efficiency, into the p53 null human H1299 cells resulted in the efficient and approximately equal expression of all chimaeric proteins ( Figure 1c). As noted in previous studies (Thomas et al, 1999), 72R polymorphic variant migrated faster than the 72P form, even when in the chimaeric form (Figure 1c), indicating that the chimaerism has not altered this biochemical property of the polymorphs.…”
Section: Generation Of Human-mouse P53 Chimaeric Constructssupporting
confidence: 82%
“…3,4 Other studies showed that the Pro-variant is less efficient in inducing apoptosis compared with the Argvariant. 25,26 This difference seems to become more pronounced with advancing age. 27 One hypothesis that has been suggested is that individuals homozygous for the Pro-allele preserve their stem cell stock as a result of decreased apoptosis and therefore maintain better cell renewal and homeostasis compared with Arg-carriers.…”
Section: Discussionmentioning
confidence: 91%
“…45 More recently, it has been shown that the ability of p53 to interact with the TFIID-associated factors TAFII32 and TAFII70 is much stronger for the Pro-72 form than for the Arg-72 form whereupon the Pro-72 form of p53 has increased transcriptional transactivation capacity. 46 In contrast, analysis of the ability of the 2 polymorphic forms of p53 to induce apoptosis suggests that the 2 polymorphic varieties, though differing in kinetics, are capable of inducing equal levels of apoptosis. 46 In another study, the Arg-72 form of the p53 protein was found to be much more susceptible to HPV E6-mediated degradation compared to the Pro-72 form.…”
Section: Discussionmentioning
confidence: 99%
“…46 In contrast, analysis of the ability of the 2 polymorphic forms of p53 to induce apoptosis suggests that the 2 polymorphic varieties, though differing in kinetics, are capable of inducing equal levels of apoptosis. 46 In another study, the Arg-72 form of the p53 protein was found to be much more susceptible to HPV E6-mediated degradation compared to the Pro-72 form. 10 In addition, analysis of mutants of p53 within a variety of tumors suggests that mutations in the Arg-72 form of p53 are more common in heterozygous individuals and that this enhances interaction with, and subsequent inactivation of, the p53 family member p73.…”
Section: Discussionmentioning
confidence: 99%